2013
DOI: 10.1371/journal.pone.0069908
|View full text |Cite
|
Sign up to set email alerts
|

The Lewis Histo-Blood Group System: Molecular Analysis of the 59T>G, 508G>A, and 1067T>A Polymorphisms in an Amazonian Population

Abstract: BackgroundThe Lewis (FUT3) gene is responsible for the expression of the Lea and Leb blood group antigens. The individuals, who not synthesize these antigens have the phenotype Lewis negative, due to the presence of some single nucleotide polymorphisms (SNPs), such as 59T>G, 508G>A and 1067T>A, whose distribution is different in various ethnic groups. Our aim was to verify the frequencies of these SNPs in an admixed population of Belém-Pará-Brazil.Materials and MethodsPolymerase chain reaction/restriction enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…Distribution of the FUT3 genotype is approximatively consistent with reported data in Chinese and other Asian populations. Nevertheless, no Asian population study has confirmed the existence of le 508 previously, which is at a frequency of 0.16% in the present study and 0.70% in an Amazonian population . le 59,508 is abundantly distributed in most populations with a frequency from 14% to 31%, but rarely found in Caucasians (1.0% and 1.5%).…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…Distribution of the FUT3 genotype is approximatively consistent with reported data in Chinese and other Asian populations. Nevertheless, no Asian population study has confirmed the existence of le 508 previously, which is at a frequency of 0.16% in the present study and 0.70% in an Amazonian population . le 59,508 is abundantly distributed in most populations with a frequency from 14% to 31%, but rarely found in Caucasians (1.0% and 1.5%).…”
Section: Resultssupporting
confidence: 49%
“…Both FUT3 and FUT2 genes have no intron in the open reading frame and fewer reactions are capable of amplification of the complete mutation region. Three pairs of PCR primers respectively specific for the FUT3 and FUT2 gene segments are shown in Table S1, and sequence design partly referred to those previously reported . For each segment amplification, 20 ng of genomic DNA was combined with the primers (7.5 μ m for forward and reverse) in a PCR system of final volume 25 μL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many mutations show a distinct geographic or ethnic distribution. In Caucasians, alleles containing T202C (Trp68Arg) and C314T (Thr105Met) mutations are common (le 202,314 ), whereas le 59 , le 59,508 , and le 59,1067 are predominant in Japan, China, South Korea, northern India, Asia, and the Brazilian Amazon (2,29,(66)(67)(68)(69)(70)(71). In African and U.S. black populations, several additional SNPs have been identified, especially G13A (Gly5Ser), G484A (Asn162Asp), G667A (Gly223Arg), and A808G (Val270Met) (69,72,73).…”
Section: Abo and Lewis Geneticsmentioning
confidence: 99%